Role of Retail Channel Management Strategy – In Context of Indian Automobile Dealerships Satisfaction - Sujay Bhalchandra,; N.D.Shinde, (International Journal of Engineering and Management Research, 2024)
Maintaining high-quality standards is crucial for dealerships to ensure ongoing business success since they play a critical role in promoting manufacturers in the marketplace. The study's objective is to highlight areas where Original Equipment Manufacturer (OEM)-Dealers relationships are lacking in relation to crucial business metrics in order to provide practical recommendations for improving OEM-Dealer collaboration. The study utilizes primary data, collected from 141 automobile dealers in Pune using a random sampling technique and structured interviews. Secondary data is gathered in order to reinforce the study's objectives. The study's aims are thoroughly justified through the use of SPSS for primary data analysis (t-tests, ANOVA, regression, and correlation) and Excel for secondary data analysis. Statistical research shows a substantial association between OEM market shares and DSI (dealer satisfaction index), with a Pearson's correlation coefficient = 0.850, signifying a highly significant relationship. Dealers linked to enterprises with larger market shares are more likely to show higher satisfaction ratings. The study emphasizes the significance of Original Equipment Manufacturer (OEM) participation in policy-making, revealing a strong link (Pearson correlation coefficient = 0.821) between dealer satisfaction and OEM’s involvement with policy decisions. The findings emphasize the essential standing of collaboration between OEMs and dealers and provide practical suggestions for improving business partnerships, leading to increased dealer satisfaction and overall success in the automotive sector.